PEKERJA PARKIR PEREMPUAN DI KOTA DUMAI (STUDI TENTANG PROSES PENETAPAN LOKASI PARKIR) - Aningsih, Indah Fitri; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This work is based on an informal jobs, a determination themselves with the business and skill which is not reached by the employment. Usually this job also more chosen by labor of the female genitalia because the characteristic that is distinctive. This work is done by men, because it is a quite hard work is done by women. But as development era, this job also chosen by many female workers especially of women that has been settling down for the sake of sufficient daily needs family. Parking worker is a person employed to monitor vehicles on the parking right as well as service payment collect the parking on the edge of a public road. There are two problems faced by workers parking lot when she worked namely environmental problems or location of work less comfortable and the occurrence of violent problems when she worked.This research aims to understand the process and what course which is one reason women workers parking in setting an election parking location and identifying several strategies workers endure women parking lot located in the city of Dumai by the use of quantitative analysis diskriptive and data collection techniques interview, as well as the sample collection methods used are census method.The time in working hours, women parking workers in the city Dumai experienced multiple forms of violence, the transfer of parking location without a permit and the dispute with various parties involved. Forms of violence suffered by parking workers is in the form of a threat, rough treatment and sexual harassment slight extent .The threat of: a lowbred remark as bluster to frighten respondents.Rough treatment: ordure, the charges and other. And sexual harassment slight extent: asked for their subscription to seduced by thugs when he was its turn around the location.Strategy is the way parking workers women to maintain any profession as a worker parking so as not experienced multiple forms of violence and the transfer of parking location. The strategy used by workers parking to prevent the occurrence of the various problems is: Be friendly with parking users and the surrounding areas, work together and filed for protection from authorities and pay a levy/parking tax coordinator on time t